Sex Differences in Perception of Economic and Dating Access - Rachel E. Hall; Khandis Blake; Ho Fai Chan; Benno Torgler; Stephen Whyte (Evolutionary Psychology)
Mating and labor markets are fundamental drivers of societal dynamics. Yet, equity of access to these domains differs between the sexes due to numerous biological, economic, psychological, and socio-cultural factors. These inequalities and their impacts can accentuate perceptions, preferences, and behaviors of males and females in different ways. Utilizing a large cross-sectional sample of those currently engaged in the Australian mating market ( n  = 1072 online daters), we explored the impact of sex and individual differences on the perceptions of men's ease of access to a decent job in the labor market (opportunity), women's economic dependence on men (economic inequality), and relative reproductive opportunity (dating access) for both sexes. Our study identifies both sex differences and symmetries in socio-economic factors (such as education level and having offspring) correlating with the perceptions of both economic and dating market access for Australian online daters. Additionally, key resource endowment indicators (income and unemployment) also reflect differences in both sexes’ perceptions of both access and gender equity. That said, our study finds that perceptions of access to both (economic and mating) markets shows far greater variation based on biological age (especially for women) than any other factor.